DIAGNOSTICS AND TREATMENT OF PRIMARY AND SECONDARY HYPERPARATHYROIDISM - M. F. Zarivchatskiy; S. A. Denisov; S. A. Blinov; A. P. Kolevatov; N. S. Teplykh (Вестник хирургии имени И.И. Грекова, 2018)
The experience of treatment of 41 patients (aged 32–67years) was presented in the article. The duration of disease was 2–5 years. Primary hyperparathyroidism was diagnosed in 16 patients and secondary — in 25. Diagnostics of the disease included clinical methods of treatment; studying levels of general and ionized calcium, phosphorus, parathormone; an ultrasound of thyroid and parathyroid glands, the substratum scintigraphy. All patients were undergone the operation. Adenomas of parathyroid glands were removed in the case of primary hyperparathyroidism including mini-access. Hyperplastic parathyroid glands (3½) were disposed in the case of secondary hyperparathyroidism. Good immediate and long-term results were obtained.